CCL5-Secreting Virtual Memory CD8+ T Cells Inversely Associate With Viral Reservoir Size in HIV‐1−Infected Individuals on Antiretroviral Therapy - Hu, Wei; Li, Yan-Jun; Zhen, Cheng; Wang, You-Yuan; Huang, Hui-Huang; Zou, Jun; Zheng, Yan-Qing; Huang, Gui-Chan; Meng, Si-Run; Jin, Jie-Hua; Li, Jing; Zhou, Ming-Ju; et al. (Frontiers in Immunology, 2022)
Recent studies highlighted that CD8+ T cells are necessary for restraining reservoir in HIV-1-infected individuals who undergo antiretroviral therapy (ART), whereas the underlying cellular and molecular mechanisms remain largely unknown. Here, we enrolled 60 virologically suppressed HIV-1-infected individuals, to assess the correlations of the effector molecules and phenotypic subsets of CD8+ T cells with HIV-1 DNA and cell-associated unspliced RNA (CA usRNA). We found that the levels of HIV-1 DNA and usRNA correlated positively with the percentage of CCL4+CCL5- CD8+ central memory cells (TCM) while negatively with CCL4-CCL5+ CD8+ terminally differentiated effector memory cells (TEMRA). Moreover, a virtual memory CD8+ T cell (TVM) subset was enriched in CCL4-CCL5+ TEMRA cells and phenotypically distinctive from CCL4+ TCM subset, supported by single-cell RNA-Seq data. Specifically, TVM cells showed superior cytotoxicity potentially driven by TBX21 and RUNX3, while CCL4+ TCM subset displayed a suppressive phenotype dominated by JUNB and CREM. In viral inhibition assays, TVM cells inhibited HIV-1 reactivation more effectively than non-TVM CD8+ T cells, which was dependent on CCL5 secretion. Our study highlights CCL5-secreting TVM cells subset as a potential determinant of HIV-1 reservoir size. This might be helpful to design CD8+ T cell-based therapeutic strategies for cure of the disease.